The Relationship of Sleep Quality with Stress Level among Hypertension Patients - Andika Abdul Malik; Diar Wiarsih; Anggi Rosmawati; Deana Sulistiani; Annisa Fithriani; Beti Rostantia; Alisa Fikri Aulia (Inspirasi Foundation, 2021)
Introduction: As many as 9.4 million people in the world suffer from hypertension, many people with hypertension ignore their disease, even though if left unchecked it will lead to more serious diseases. Objective: This research aims to is study was to find out whether there is a relationship between sleep quality and stress levels in patients with hypertension. Method: The type of research used is quantitative analysis using a cross sectional design. The sampling technique used is simple random sampling. The research population was 100 people and the total sample was 50 people. The research instrument was carried out by measuring blood pressure and distributing questionnaires. Result: The results showed that the majority of respondents had better sleep quality than the average of 5 people (10%). While the stress level of respondents in the mild stress category was 23 people (46%). Conclusion: From the results of the analysis carried out, it can be concluded that the relationship between sleep quality and stress levels in patients with hypertension is not significant or has no relationship with p value = 0.340.